The impact of building the capital structure on determining the company's value within the framework of the signaling and exchange theories - حسام كامل سلطان; علي احمد فارس (Iraqi Journal for Administrative Sciences, 2024)
The study aims to explore the effect of building capital structure in determining the value of the firm. The study relied on two theories of the modern structure of capital, namely, the theory of the Trade-off between the financial risk of debt (the cost of bankruptcy and financial hardship) and the tax shield achieved The theory of signaling refers to how managers send special signals to investors indirectly shows the ability of the firm in the near future depending on the information sent in the signaling . The study is based on a set of reports and financial statements published for a group of firm listed in the Iraq Stock Exchange, Based on the availability of data for the study period (2005-2014), the study used a variety of financial and statistical means to achieve its objectives through the use of Excel and SPSS programs. The study found that there was a clear decline during the period of study in the profitability of firm , which negatively affected their value, and these firm do not use borrowing enough to achieve the goals of profitability. The study recommended the need for a more open and expanded borrowing policy to maximize the benefits of tax benefits.